STAR case competition 2020 : Rotterdam 2020 - Geoffroy, Paula Arellano (London : Rotterdam School of Management, Erasmus University, 2020)
Inequality was one of the main causes of the upheavals and massive protests that occurred in 2019 and which are still ongoing in many cities in the world. The United Nations (UN) recognized that inequality threatens long-term socio-economic development and can breed violence, insecurity, disease and environmental degradation. "Leave no one behind" is the call of the UN 2030 Agenda for Sustainable Development, and reducing inequality is Sustainable Development Goal number 10.Inequality is closely linked to poverty in Rotterdam, which has the highest poverty rate in the Netherlands (10.9%) and the highest share in the country of children living in low-income households (17.5%). Inequality and segregation in the city are characterized by high unemployment, a high density of manual workers and low educational attainment. These problems are explained in part by Rotterdam's status as the largest seaport in Europe-once the largest in the world-which in the past attracted unskilled and semi-skilled immigrants who stayed and passed on impoverished conditions to new generations. Currently half of Rotterdam's population is of non-Dutch origin. In recent decades the city also underwent urban renewal, pushing low income people to the outskirts of the city through gentrification.Addressing inequality is a complex and long-term matter, but the trends on a possible solution point to a wide collaboration between all stakeholders involved in society. JINC, Voor Goed and Coca-Cola-a non-profit, a government-partnered, and a corporate organization-are together very clear that addressing inequality not only involves big challenges (securing the financial resources to scale up, creating poverty awareness, keeping social entrepreneurs in the city, measuring the impacts, etc.), but that it also represents huge opportunities to build partnerships and foster collaborative ways of working. How can they manage to work together towards a more equal and inclusive society?
Originally Published InGeoffroy, P. A. (2020). STAR Case Competition 2020: Rotterdam 2020: Bridging the Gap of Inequality. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sustainable development -- Netherlands -- Rotterdam -- Case studies; Income distribution -- Netherlands -- Rotterdam -- Case studies; Social entrepreneurship -- Netherlands -- Rotterdam -- Case studies